A potassium-rich iron hexacyanoferrate/dipotassium terephthalate@carbon nanotube composite used for K-ion full-cells with an optimized electrolyte. Issue 36 (29th August 2017) - Liao, Jiaying; Hu, Qiao; Yu, Yingtao; Wang, Heyang; Tang, Zhongfeng; Wen, Zhaoyin; Chen, Chunhua
Abstract : K-ion batteries, as an emerging battery system, have attracted tremendous attention in the research community. Abstract : K-ion batteries, as an emerging battery system, have attracted tremendous attention in the research community. Herein, we report a K-ion full-cell based on a nano-sized K1.92 Fe[Fe(CN)6 ]0.94 ·0.5H2 O cathode, dipotassium terephthalate (K2 TP)@carbon nanotube (CNT) anode and an optimized electrolyte. K1.92 Fe[Fe(CN)6 ]0.94 ·0.5H2 O delivers a high capacity of 133 mA h g −1 with 92.8% capacity retention after 200 cycles and high coulombic efficiency of 98.5%. The side reactions of K metal with the electrolyte are suppressed in KClO4 /propylene carbonate (PC). The K2 TP nanosheets grown in situ on the CNT show a high reversible capacity of about 250 mA h g −1 and an ultra-high rate capability. The full-cells based on them are well cycled in a DME-based electrolyte and show a great promise for large-scale energy storage.